Exploring the connectedness between major volatility indexes and worldwide sustainable investments - Xu, D.; Hu, Y.; Oxley, Leslie; Lin, B.; He, Y. (2025)
This paper examines the dynamic connectedness between various measures of volatility indexes (e.g., Engle and Campos-Martins (2023)’s global common volatility index (COVOL), VIX, OVX, GVZ) and worldwide ESG leaders’ equity markets, using an aggregated connectedness approach for the period January 2014 to April 2023. Several novel findings are presented. First, the COVID-19 pandemic has a significant impact on the dynamic total connectedness of the system compared to other major global events. Second, the COVOL is a receiver of aggregated global ESG while VIX is a major transmitter. Third, based on the stage of economic development for each ESG market, the aggregated developed-country ESG group plays a more dominant role in the transmission channel. Fourth, based on aggregated ESG markets by region, the VIX is the primary transmitter to four regional ESGs. Last, European ESG market has low connectedness with the major volatility indexes and other regional ESGs. These findings have important and practical implications for investors and portfolio managers in formulating effective risk management strategies for ESG-related investments.